Endocrinology and auxology of sibships with non-classical congenital adrenal hyperplasia. Issue 5 (May 1996) - Cameron, F J; Tebbutt, N; Montalto, J; Yong, A B; Zacharin, M; Best, J D; Warne, G L
Abstract : The symptoms, auxological characteristics, and stimulated 17-hydroxyprogesterone (17-OHP) concentrations in a group of patients with non-classical 21-hydroxylase deficiency (NCCAH) were compared with those of their siblings. Ten index cases consisting of nine females and one male patient aged 3-33 years and 16 siblings were studied. In the sibling group five subjects were slightly virilised and of these, two females were found to have NCCAH according to their stimulated 17-OHP concentrations. The remaining nine siblings, who were not virilised, all had normal stimulated 17-OHP concentrations. Among the total NCCAH group (index cases and affected siblings) eight patients had the diagnosis made within two years of the onset of symptoms. In four patients diagnosis was delayed until adulthood. In seven patients investigated, bone age was significantly increased before treatment. The mean height and body mass index Z scores of the affected patients as a total group or when divided according to skeletal maturity were not significantly different from either the normal mean or from their unaffected siblings. Virilised siblings of patients with NCCAH should have stimulated 17-OHP levels measured to exclude the disease. Patients with NCCAH do not appear to be at risk of short adult stature despite increased bone age in childhood.